2021
DOI: 10.1177/0040517521993484
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel segmented-pie microfibers from copper-carbon nanoparticles and polyamide composite for antimicrobial textiles application

Abstract: Development of novel antibacterial fibers with mass production is urgently required in the technical textiles industry. In this paper, a series of segmented-pie composite microfibers based on polyamide 6 (PA6) and different amounts of copper–carbon nanoparticles (CuCNPs) were fabricated by utilizing a melt-spinning apparatus with twin-screw extruders. The encapsulation of CuCNPs and the formation of segmented-pie structure of as-prepared PA6/CuCNP microfibers were confirmed. The CuCNPs or their agglomeration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…First of all, the dominant peaks were associated with strong C, O, and N signals in synthetic fibers, as well as with complex Cu and Se X-ray lines (Figure 11). Other investigators [29][30][31] also reported peaks corresponding to C, O, and N obtained from the analysis of untreated PAN fibers, PA6 fibers [32], PA66 [33], and PES fibers [34]. The Cu and Se peaks emanating from the Cu x Se coatings confirmed the formation of a welldefined thin coating layer.…”
Section: Sem and Edx Analysismentioning
confidence: 81%
See 1 more Smart Citation
“…First of all, the dominant peaks were associated with strong C, O, and N signals in synthetic fibers, as well as with complex Cu and Se X-ray lines (Figure 11). Other investigators [29][30][31] also reported peaks corresponding to C, O, and N obtained from the analysis of untreated PAN fibers, PA6 fibers [32], PA66 [33], and PES fibers [34]. The Cu and Se peaks emanating from the Cu x Se coatings confirmed the formation of a welldefined thin coating layer.…”
Section: Sem and Edx Analysismentioning
confidence: 81%
“…Other investigators [29][30][31] also reported peaks corresponding to C, O, and N obtained from the analysis of untreated PAN fibers, PA6 fibers [32], PA66 [33], and PES fibers [34]. The Cu and Se peaks emanating from the CuxSe coatings confirmed the formation of a well-defined thin coating layer.…”
Section: Sem and Edx Analysismentioning
confidence: 82%
“…Wound infection and the spread of infection through hospital textiles are serious concerns in hospitals. Therefore, several studies have been conducted to produce antimicrobial textiles in the past few years [ [3] , [4] , [5] ]. The main challenge of this research is the requirement for materials that do not cause toxicity, allergies, or sensitivities.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the scientific literature recorded an increase in the number of articles reporting on antimicrobial textiles and their specific finishing, reagents, and processing. A bibliometric analysis indicated in 2021 a number of publications of 534 articles per year [5], but the domain is very active and the rapid progress is abundantly documented by the most recent literature reports, which also illustrate the variety of new features connected to the subject [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introduction 1general Backgroundmentioning
confidence: 99%